Understanding the Molecular Mechanisms of Incomptine A in Treating Non-Hodgkin Lymphoma Associated with U-937 Cells: Bioinformatics Approaches, Part I - Fernando Calzada; Normand García-Hernández; Elihú Bautista; José Manuel Sánchez-López; Miguel Valdes; Claudia Velázquez; Elizabeth Barbosa (Pharmaceuticals)
Background: Incomptine A (IA) has been reported to have cytotoxic activity in non-Hodgkin lymphoma cancer cell lines and have effects on U-937 cells, including the induction of apoptosis, the production of reactive oxygen species, and the inhibition of glycolytic enzymes. Also, IA has cytotoxic activity in the triple-negative subtypes, HER2+, and luminal A of breast cancer cells, with its properties being associated with an effect on the antiapoptotic function of Hexokinase II (HKII). Objectives: In this research, we reviewed the altered levels of proteins present in the lymph nodes of male Balb/c mice inoculated with U-937 cells and treated with IA or methotrexate, as well as mice only inoculated with cancer cells. Methods: Five approaches, including Tandem Mass Tag (TMT), Gene ontology (GO), Reactome, KEGG pathway analysis, and molecular docking, were used. Results: TMT showed that 74 proteins were differentially expressed, out of which 12 presented overexpression (FC ≥ 1.5) and 62 were under expressed (FC ≤ 0.67). In general, the TMT approach showed that IA had a better effect on proteins than methotrexate. Gene ontology, Reactome, and KEGG pathway analysis showed that proteins with altered levels may be implicated in several processes, including gene silencing by RNA, oxidative phosphorylation, glycolysis/gluconeogenesis, cytoskeleton organization, and ATP metabolic and energetic processes. The molecular docking analysis, which used 23 altered proteins as targets, revealed that IA interacted with all the proteins used. Conclusions: The results obtained using the five bioinformatic approaches provide information and show that IA could be used to treat non-Hodgkin lymphoma induced with the U-937 cell line. Also, it could provide a basis for future research and the development of clinical trials.